Question about Texas Instruments TI-89 Calculator

If I'm not misunderstanding you, this isn't an equation you need a calculator for, it's basic algebra. Factor out the z from the right side and divide x by the remaining binomial. That's as far as you can go with an equation like this unless you have specific values for these variables, unless this is a question from college Cal 3-4, which I have not yet completed.

Posted on Oct 28, 2008

There is nothing to solve here.You just have an expression with two letters; you have no equation to solve because you need an = sign.

Sep 07, 2013 | Calculators

Your scientific calculator is unable to solve complex equation with complex coefficients. You should try to solve by hand directly using the quadratic formula or by factoring the polynomial in z

failing that, another way would be to set z=x+iy, substitute this for z, carry out the algebra and try to separate real and imaginary parts. But your two equations will constitute a system of two quadratic equations. I am not aware of any general method to solve coupled nonlinear equations.

Good luck.

failing that, another way would be to set z=x+iy, substitute this for z, carry out the algebra and try to separate real and imaginary parts. But your two equations will constitute a system of two quadratic equations. I am not aware of any general method to solve coupled nonlinear equations.

Good luck.

Dec 20, 2012 | Casio FX-115ES Scientific Calculator

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

Apply what you learned, especially that this system is quite simple.

Elimination

1. entails eliminating one variable to find (in this case) a single equation involving the other variable.

2. Solve that new equation, meaning isolate the variable that was not eliminated.

3. Substitute the value found in the last step and replace it in one of the original equation to obtain the other variable.

x+y=10

x-y=-6

Add the left sides to get x+y+x-y=2x

Add the right sides of the system to obtain 10+(-6)=4

Write Sum of left sides =Sum of right sides or 2x=4.

Since this new equation involves only x, you can solve it for x, getting x=4/2=2

Now you know the value of x (=2)

Take one of the original equations (for example x+y=10) and put 2 in place of x.

The equation becomes 2+y=10

Solve it to obtain y=10-2=8

Thus your solution is x=2, y=8

Check: use one equation in which you substitute 2 for x and 8 for y: x-y=-6 becomes 2-8=-6

Verified.

In the general case you will have to multiply by certain values to obtain opposite coefficients for the same variable. Here that was not necessary because the coefficient of y is 1 in the first equation and -1 in the second.

Elimination

1. entails eliminating one variable to find (in this case) a single equation involving the other variable.

2. Solve that new equation, meaning isolate the variable that was not eliminated.

3. Substitute the value found in the last step and replace it in one of the original equation to obtain the other variable.

x+y=10

x-y=-6

Add the left sides to get x+y+x-y=2x

Add the right sides of the system to obtain 10+(-6)=4

Write Sum of left sides =Sum of right sides or 2x=4.

Since this new equation involves only x, you can solve it for x, getting x=4/2=2

Now you know the value of x (=2)

Take one of the original equations (for example x+y=10) and put 2 in place of x.

The equation becomes 2+y=10

Solve it to obtain y=10-2=8

Thus your solution is x=2, y=8

Check: use one equation in which you substitute 2 for x and 8 for y: x-y=-6 becomes 2-8=-6

Verified.

In the general case you will have to multiply by certain values to obtain opposite coefficients for the same variable. Here that was not necessary because the coefficient of y is 1 in the first equation and -1 in the second.

Aug 16, 2011 | Casio Calculators

This calculator doesn't really support a solver like that. You can use Woflram Alpha to solve equations like that really quickly. Example

There are more expensive calculators that will solve these types of equations, but I would recommend just using Wolfram Alpha whenever you need a solution to a math problem.

There are more expensive calculators that will solve these types of equations, but I would recommend just using Wolfram Alpha whenever you need a solution to a math problem.

Mar 02, 2011 | Casio FX-115ES Scientific Calculator

It looks like overkill to use the calculator to solve this first order linear equation but I will show you how to use the Solve function available on this calculator.

First solution: Pen and paper.

Use the properties of proportions:

Let a, b, c, and d numbers, with b, and d not equal to 0

if a/b=c/d then a*d=b*c

To apply it to your case, you set a=2.5, b=7, c=x, and d=10.

This gives 2.5*10=7*x

Dividing both members of the equation by 7 yields x=25/7.

Using the SOLVE program

If you are not happy with the solution (L-R different from 0), or the calculator failed to return a solution, you can press [SHIFT][CALC] (SOLVE) to restart with a better guess.

First solution: Pen and paper.

Use the properties of proportions:

Let a, b, c, and d numbers, with b, and d not equal to 0

if a/b=c/d then a*d=b*c

To apply it to your case, you set a=2.5, b=7, c=x, and d=10.

This gives 2.5*10=7*x

Dividing both members of the equation by 7 yields x=25/7.

Using the SOLVE program

- Calculator should be in computational mode: Press [MODE][1:COMP]
- Type in the equation in the way described below:
- You will need to use the key sequence [ALPHA][CALC] (=) to insert the = sign, the one at the top left, not the one at the bottom right.
- You will need to use the sequence [SHIFT][CALC] (SOLVE) to order the calculator to start solving your equation.
- You will need the key sequence [ALPHA] [)] to insert the X variable.
- Now that you have been alerted to the sequaences you will need, here is how to enter your equation.
- 2.5/7 [ALPHA][CALC] (=) [ALPHA] [ ) ] (X) /10
- While the above sequence is in the command line with the cursor still blinking to the right of the 0, press [SHIFT][CALC] to access the (SOLVE) command.
- The calculator displays in the top line of the dispaly "Solve for X". At the bottom there would be some old (irrelevant value).
- At this point you are expected to enter a value for your initial guess.
- You can for example enter 2 and press [=] at the bottom right. If you do not type a guess, the calculator uses the old (irrelevant) value as initial guess.
- So you enter initial guess 2 and press the [=/EXE] key at the bottom.
- After a while (could be short , if the initial guess is inspired) the calculator returns with the solution.
- The solution display screen recalls your equation on the top line,
- X=3.571428571 on the middle line, and
- L-R= 0 on the bottom line.

If you are not happy with the solution (L-R different from 0), or the calculator failed to return a solution, you can press [SHIFT][CALC] (SOLVE) to restart with a better guess.

Feb 10, 2010 | Casio FX-115ES Scientific Calculator

Hello,

Sorry, but what you wrote is not an equation but a polynomial expression. You want to solve the equation x^4+5x^3-3x^2-43x-60 =0.

The solve( command, can only be used with real numbers.

The** solve(** is available through the CATALOG :
[2nd][CATALOG], scroll down till you reach the command. Highlight it
and press [ENTER]. The command echodes on main screen as **solve(** .

You complete the command by entering the expression (not the equation), the name of the variable you solve for, the initial guess , and { lower limit, upper limit} between curly brackets, and the closing parenthesis.

Exemple:

**solve (x^4+5x^3-3x^2-43x-60 ****, x,0 {-5,0} ) [ENTER]**

should give you the negative root,

**solve (x^4+5x^3-3x^2-43x-60 ****, x,0 {0,5} ) [ENTER]**

should give you the positive root.

It is implied that the expression is 0, so you should not insert =0, otherwise you get an error. Here for the lower limit is -5 you must use the change sign symbol (-) under the 3 key, not the regular MINUS.

You may ask how I knew that there were two roots when the equation is a quartic? By first graphing it to have an idea about where the roots lie and how many there are. You should always do that to speed up the search.

There is another way to zoom in on the roots: by drawing the graph and using the tools accessible under the [2nd][CALC] menu, namely the option [2:Zero]

The resolution of the TI83/84 is not good enough for this function that grows too fast, but I am inserting a picture of the curve from another calculator with a much better resolution.

Hope it helps.

Sorry, but what you wrote is not an equation but a polynomial expression. You want to solve the equation x^4+5x^3-3x^2-43x-60 =0.

The solve( command, can only be used with real numbers.

The

You complete the command by entering the expression (not the equation), the name of the variable you solve for, the initial guess , and { lower limit, upper limit} between curly brackets, and the closing parenthesis.

Exemple:

should give you the negative root,

should give you the positive root.

It is implied that the expression is 0, so you should not insert =0, otherwise you get an error. Here for the lower limit is -5 you must use the change sign symbol (-) under the 3 key, not the regular MINUS.

You may ask how I knew that there were two roots when the equation is a quartic? By first graphing it to have an idea about where the roots lie and how many there are. You should always do that to speed up the search.

There is another way to zoom in on the roots: by drawing the graph and using the tools accessible under the [2nd][CALC] menu, namely the option [2:Zero]

The resolution of the TI83/84 is not good enough for this function that grows too fast, but I am inserting a picture of the curve from another calculator with a much better resolution.

Hope it helps.

Oct 18, 2009 | Texas Instruments TI-83 Plus Calculator

Hello,

Sorry this calculator cannot solve equations. It does not have the program. It does not know how to do those things. However it can calculate.**Before you can use the calculator you must prepare all yourself. **When you have solved the problem, you ask the calculator to compute the value of what you found.

Let us clean the equation a bit

2(x-4) -5x=-5

Get rid of the parentheses 2(x-4) becomes 2x-2*4=2x-8 .Put that result where it was in equation

2x-8 -5x=-5

Group together the terms that have x in them 2x-5x=-3x

Then

2x-8-5x=-5, becomes -3x-8=-5

You want to isolate the term with x (have it on one side, and the others on the other side) -3x= -5 -(-8)= -5+8 =3.

The equation becomes

-3x=3 Thus**-x=3/3=1 and x=-1.**

**In general you would have obtained x= (some number/some other number) and that is where the calculator would intervene.**

Hope it helps.

Sorry this calculator cannot solve equations. It does not have the program. It does not know how to do those things. However it can calculate.

Let us clean the equation a bit

2(x-4) -5x=-5

Get rid of the parentheses 2(x-4) becomes 2x-2*4=2x-8 .Put that result where it was in equation

2x-8 -5x=-5

Group together the terms that have x in them 2x-5x=-3x

Then

2x-8-5x=-5, becomes -3x-8=-5

You want to isolate the term with x (have it on one side, and the others on the other side) -3x= -5 -(-8)= -5+8 =3.

The equation becomes

-3x=3 Thus

Hope it helps.

Sep 11, 2009 | Texas Instruments TI-30XA Calculator

Hello,

I do not understand what you mean by solve complex equations, but if you want to manipulate complex numbers here are the tools you need to enter your complex numbers. Operations and function evaluations do not need special symbols.

Hope it helps.

I do not understand what you mean by solve complex equations, but if you want to manipulate complex numbers here are the tools you need to enter your complex numbers. Operations and function evaluations do not need special symbols.

Hope it helps.

Oct 31, 2008 | Casio FX-9860G Graphic Calculator

Just plug in one side of the equation and find the answer. Then plug in the other side and compare answers.

Feb 19, 2008 | Texas Instruments TI-89 Calculator

149 people viewed this question

Usually answered in minutes!

×